Analisis Kontribusi Retribusi Daerah dan Laba Bumd terhadap Pendapatan Asli Daerah (PAD) di Provinsi Kalimantan Selatan - Lazuardi, Muhammad (PPJP ULM, 2019)
This study aims to determine the level of contribution and effectiveness of regional retribution and profit of regional owned enterprises to LOR and efforts that can be done to improve the acceptance of local retribution and gain of regional owned enterprises in South Kalimantan Province. The research method used is the descriptive quantitative method. This study indicates that regional retribution and profits of local owned enterprises to LOR in South Kalimantan Province from 2014-2016 are still low. In the 2014-2016 period, the effectiveness of regional retribution and regional-owned enterprises was beneficial. This means that the realization of local levies and profits of regional owned enterprises in the 2014-2015 period always reaches the target. Then efforts can be made to increase revenues and the contribution of local retribution to LOR, namely through intensification and extensification. Simultaneously, the effort to improve regionally owned enterprises' income is through rearrangement and improvement of company management, training, or coaching of regional owned enterprises employees.